2019
DOI: 10.1186/s12876-019-0995-z
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir add-on to ribavirin for chronic hepatitis E in a cirrhotic liver transplant recipient: a case report

Abstract: Background Chronic hepatitis E represents an emerging challenge in organ transplantation, as there are currently no established treatment options for patients who fail to clear hepatitis E virus (HEV) following reduction of immunosuppressive therapy and/or treatment with ribavirin. Sofosbuvir has shown antiviral activity against HEV in vitro but clinical utility in vivo is unknown. Case presentation We describe a 57-year-old liver transplant recipient with decompensated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Even after a long treatment period of 24 weeks, HEV remained detectable at low levels and was not cleared from the feces. This is in line with the findings of Valk et al [9] and Fraga et al [11], by whom an antiviral effect of sofosbuvir was observed; however, SVR was not achieved.…”
Section: Discussionsupporting
confidence: 93%
“…Even after a long treatment period of 24 weeks, HEV remained detectable at low levels and was not cleared from the feces. This is in line with the findings of Valk et al [9] and Fraga et al [11], by whom an antiviral effect of sofosbuvir was observed; however, SVR was not achieved.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, again in this case although the addition of sofosbuvir to ribavirin did demonstrate heightened inhibition of viral replication this combination at the doses administered (a relatively low ribavirin dose due to anaemia and impaired renal function) failed to achieve viral eradication. Similar findings were observed in a case reported by Fraga et al in which a 57 year old liver transplant recipient who was diagnosed with a genotype 3 chronic HEV infection and who failed to achieve undetectable HEV RNA levels in plasma despite 5 months of ribavirin monotherapy (doses not specified), had sofosbuvir (400mg/day) added for a period of 24 weeks 44 . HEV RNA became undetectable in plasma shortly after the addition of sofosbuvir and remained undetectable over the 24 week period however HEV RNA was detectable in stool towards the end of the 24 week period (having become initially undetectable in stool after the addition of sofosbuvir).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Drafting of the manuscript were done by MC, SH, PB, SP and HW, critical revision of the manuscript was performed by all authors, administrative support: AL and MPM. Tobias Müller 7 Patrick Behrendt 1,4 Felix Piecha 5 Julia Benckert 7 Daniel Todt 8 Eike Steinmann 8 Armin Papkalla 9 Maria von Karpowitz 10 Armin Koch 10 Ansgar Lohse 5,6 Svenja Hardtke 3 Michael P. Manns 1,3 Heiner Wedemeyer…”
Section: Financial Supportmentioning
confidence: 99%